Numerical modeling predicts seismic resonances in the magma chamber-conduit system due to wavefield capturing - Limberger, Fabian; Rümpker, Georg (Volcanica, 2024)
This study utilizes 3D numerical models to simulate seismic resonances in a volcanic edifice, arising from the interaction between an externally excited wavefield and a magma chamber-conduit system. The magma chamber and conduit efficiently capture the incident wavefield of both P- and S-waves, excited by a high-frequency (~10 Hz) earthquake located within the edifice. Due to multiple internal reflections off the boundaries of the chamber and conduit, prolonged reverberations occur, which are guided along the conduit. Temporal and spectral analyses of synthetic seismograms illustrate that models with larger chambers and wider conduits consistently yield larger resonance amplitudes at distinct frequencies. Our models indicate that a larger magma chamber can produce an intensified scattered wavefield with a broad frequency range, observable up to several hundred meters away from the central conduit. Generally, these externally initiated ‘calabash resonances’ may appear as tremor-like signals at seismometers on the edifice, accompanying more conventional seismic events in its proximity.